4,4′-Di-tert-butyl-2,2′-[(3aRS,7aRS)-2,3,3a,4,5,6,7,7a-octahydro-1H-1,3-benzimidazole-1,3-diyl)bis(methylene)]diphenol - Rivera, Augusto (International Union of Crystallography, 2011)
In the title compound, C(29)H(42)N(2)O(2), the heterocyclic ring has a twist conformation. The cyclohexane ring adopts a chair conformation. The dihedral angle between the aromatic rings is 32.74 (6)°. The molecular conformation is stabilized by two intramolecular O—H⋯N hydrogen bonds with graph-set motif S(6). The crystal packing is stabilized by C—H⋯O and C—H⋯π interactions.